Optimisation of organic matter removal from landfill leachate using ferrous (II)/Persulfate (PS) system - Samsul, Nabilah; Isa, Mohamed Hasnain; Shams, Shahriar; Hj Md. Juani, Rozeana; Jami, Mohammed Saedi (AIP Publishing, 2023)
Fe (II) activated Persulfate (PS) enhanced with reducing agent, Hydroxylamine (HA) was selected in this study for landfill leachate treatment. Central composite design (CCD) under response surface methodology (RSM) was used to design the experiment and predict the optimum operating conditions. The effects of independent parameters Persulfate dose, Fe (II) Dose, Hydroxylamine dose, pH level and Reaction time were investigated with effluent COD concentration and COD removal efficiency as responses. Based on the ANOVA analysis, it was found that all the parameters and their interactions played a role in the treatment of landfill leachate. The optimum treatment condition was 0.58 μM, 38 μM, 15 μM, 2.13, and 31 minutes for PS dose, Fe (II) dose, Hydroxylamine dose, pH level and reaction time, respectively. The optimum condition was predicted to achieve effluent COD of 642 mg/L and COD Removal of 56%. The experimental values obtained under optimum conditions were 967 mg/L and 70%, respectively; variations attributed to the varying influent composition of leachate. The study found that Fe (II) activated PS enhanced with Hydroxylamine can be used to remove COD from landfill leachate.